2022
DOI: 10.3390/metabo12030233
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights of Mitochondrial Dysfunction in Amyotrophic Lateral Sclerosis: An Update on a Lasting Relationship

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease characterized by progressive loss of the upper and lower motor neurons. Despite the increasing effort in understanding the etiopathology of ALS, it still remains an obscure disease, and no therapies are currently available to halt its progression. Following the discovery of the first gene associated with familial forms of ALS, Cu–Zn superoxide dismutase, it appeared evident that mitochondria were key elements in the onset of the pathology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 171 publications
(225 reference statements)
0
8
0
Order By: Relevance
“…Circulating contents of cholesterol, triglycerides and fatty acids were also found to be strongly altered in male Chchd10 S59L/+ mice ( Table 1 ), those alterations are known to occur over the course of ALS reflecting the metabolic environment [25]. This study showed that CHCHD10 S59L mutation is related to ALS phenotype with some specific known plasma biomarkers which correlated with described pathomechanisms of ALS [26, 27].…”
Section: Discussionmentioning
confidence: 73%
“…Circulating contents of cholesterol, triglycerides and fatty acids were also found to be strongly altered in male Chchd10 S59L/+ mice ( Table 1 ), those alterations are known to occur over the course of ALS reflecting the metabolic environment [25]. This study showed that CHCHD10 S59L mutation is related to ALS phenotype with some specific known plasma biomarkers which correlated with described pathomechanisms of ALS [26, 27].…”
Section: Discussionmentioning
confidence: 73%
“…4a). These terms include ‘ATP metabolic process’ [114], ‘gluconeogenesis’, ‘mitochondrial calcium ion transport’ [69, 96], ‘glycolytic process’ [131], ‘glycosphingolipid metabolic process’ [19, 58], ‘mitophagy’ [41, 79, 122], ‘positive regulation of mitochondrial fission’ [6, 71], ‘mitochondrial matrix’ [125], ‘mitochondrial membrane’ [25, 125], ‘integral component of mitochondrial inner membrane’ [25], ‘integral component of mitochondrial outer membrane’ [25], ‘protein import into mitochondrial matrix’ [75, 76], ‘negative regulation of amino acid transport’, ‘branchedchain amino acid catabolic process’ [155], ‘peroxisome’ [43, 53], ‘peroxisomal matrix’ [43, 53], all of which point toward altered energy metabolism and mitochondrial dysfunction. Additionally, categories related to cells’ cytoskeletal structure, such as ‘actin filament-based movement’, ‘apical dendrite’ [50], ‘microtubule associated complex’ [50, 147], and ‘anchored component of membrane’ are also implicated in the disease, which point to the structural dysregulations happening in the cells causing axonal transport disturbance [77], impairment of information integration in cells [50], and impairing cell adhesion.…”
Section: Resultsmentioning
confidence: 99%
“…2 Hemodynamic similarity: Hemodynamic similarity, often referred to as functional connectivity, summarizes the similarity across brain regions in terms of the synchronization and similarity of their co-fluctuation in the BOLD signal. The data incorporated to build the connectome comes from 326 unrelated healthy participants (145 males; age: [22][23][24][25][26][27][28][29][30][31][32][33][34][35] in the Human Connectome Project (HCP-S900 release), scanned using a 3T Connectome Skyra scanner [136]. In this dataset, each participant has undergone four 15-minute resting-state functional MRI scans, each with a TR of 720 ms. Data is preprocessed using the HCP minimal preprocessing pipeline.…”
Section: Network Reconstructionmentioning
confidence: 99%
“…Furthermore, Combo upregulated expression of VCP , a protein whose loss of function causes fALS and other degenerative disorders (40). Combo increased the expression of several subunits of mitochondrial respiratory chain complexes, which could have beneficial effects on bioenergetic capacity, known to be impaired in both genetic and sporadic forms of ALS (82). We identified several genes connected to RNA pol II transcription strongly downregulated by Combo, including YBX1 and FXR1 .…”
Section: Discussionmentioning
confidence: 99%